2007 Iran nuclear NIE: more of the story. Issue 2 (23rd February 2021) - Fingar, Thomas
ABSTRACT: The 2007 Iran nuclear NIE has been revalidated many times but was extremely controversial at the time. Contrary to the expectations and wishes of the Intelligence Community, the President ordered declassification of the key judgments (3 pages of a 140-page analysis). This article examines the aftermath of that decision, including Congressional praise and criticism, ad hominem attacks seeking to discredit the analysis by attacking individuals, and lasting consequences that strengthen the case for delaying the release of intelligence assessments on controversial subjects.